(untitled) (Palíndromo, 2019)
We propose an analysis of the Tres Aguas project, starting from the presen-tation of a series of events. The reflection addresses three aspects: the relationship between past and present, the city as a place of distribution of the sensible and art in public space. To support our ap-proach, we rely on Jacques Rancière.